2011
DOI: 10.1080/09544828.2011.603296
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a technical function grammar oriented to biomimetic

Abstract: Knowledge transfer from biologists to engineers is one of the main obstacles to the diffusion of biomimetic. An approach to overcome this obstacle is presented and discussed. This approach is based on a construct to describe high-level engineering functions stored in a relational database together with a species grouping based on a functional classification, the corresponding biological solutions and the ‘official’ taxonomy.\ud Several relationships among the keys allow extracting and organising the stored kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…, Noun . schema (Pahl et al, 2007), and to some related International Journal of Design Creativity and Innovation 5 evolutions (Rosa et al, 2011). Nevertheless, this way of storing function definition does not seem in contrast with the theoretical definition.…”
Section: Sbf Models In Bid: Danementioning
confidence: 96%
See 2 more Smart Citations
“…, Noun . schema (Pahl et al, 2007), and to some related International Journal of Design Creativity and Innovation 5 evolutions (Rosa et al, 2011). Nevertheless, this way of storing function definition does not seem in contrast with the theoretical definition.…”
Section: Sbf Models In Bid: Danementioning
confidence: 96%
“…These reflections comply with the use of Organ to represent the International Journal of Design Creativity and Innovation 7 system structure, as proposed by the authors of the model in Srinivasan, Chakrabarti, and Lindemann (2012). It is also worth noting that the environment is explicitly mentioned, recognizing its fundamental importance in biological phenomena (Rosa et al, 2011;Vattam, Wiltgen, et al, 2010). Analyzing Input definitions, it can be concluded that an Input is a particular property of the environment that triggers the Physical Effect, thus producing the Physical Phenomenon; as such, the Input should be distinguished from the system properties that enable the Physical Effect and are described by the Organ.…”
Section: Causal Models: Sapphirementioning
confidence: 97%
See 1 more Smart Citation
“…To effectively search for concepts of biological species, Rosa et al (2011) develop a structured database of these and group these using high-level functions that are represented using <verb, noun, predicate> where the predicate is represented as <preposition, noun>. Vandevenne et al (2015, pp.…”
Section: Reviewmentioning
confidence: 99%
“…The 'Proposal of a technical function grammar oriented to biomimetic' presented by Rosa et al (2011) aims to remove the barriers that hamper designers in their reasoning with analogies by stimulating and inspiring them with knowledge available in another domain. Towards this end, the authors present an extension of the standard verb and object type of function formulation and show how their conceptualisation is operationalised as a database-driven computer system with interfaces tailored to engineers and biologists, respectively.…”
mentioning
confidence: 99%